(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article reveals such important aspects as the term “media”, the history of the emergence of the media (written press, radio, television), the role and significance of newspapers, magazines, radio stations, television channels in the past and today. The article was written to draw attention to the need for the existence of media in modern life.